Targeting of the MET receptor tyrosine kinase by small molecule inhibitors leads to MET accumulation by impairing the receptor downregulation. Issue 5 (17th January 2014) - Leiser, Dominic; Pochon, Benoît; Blank-Liss, Wieslawa; Francica, Paola; Glück, Astrid A.; Aebersold, Daniel M.; Zimmer, Yitzhak; Medová, Michaela
Abstract : The MET receptor tyrosine kinase is deregulated primarily via overexpression or point mutations in various human cancers and different strategies for MET inhibition are currently evaluated in clinical trials. We observed by Western blot analysis and by Flow cytometry that MET inhibition by different MET small molecule inhibitors surprisingly increases in a dose‐dependent manner total MET levels in treated cells. Mechanistically, this inhibition‐related MET accumulation was associated with reduced Tyr1003 phosphorylation and MET physical association with the CBL ubiquitin ligase with concomitant decrease in MET ubiquitination. These data may suggest careful consideration for design of anti‐MET clinical protocols. Abstract : MET inhibition by MET small molecule inhibitors increases total MET levels. MET inhibition by MET small molecule inhibitors reduces MET Tyr1003 phosphorylation. Inhibition of MET decreases MET physical association with the CBL ubiquitin ligase. MET inhibition is associated with its decreased ubiquitination.